Bekerja Tanpa Batas Ruang: Studi Persepsi Pegawai atas Transformasi Sistem Kerja di Masa Pandemi - Parwitaningsih; H.I. Bambang Prasetyo; Nur Hayati; Grace Prima Apriani Sihombing (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
The COVID-19 pandemic has driven significant transformation in the global work system, particularly through the implementation of Work From Home (WFH), Work From Anywhere (WFA), Work From Office (WFO), and hybrid models. This study aims to analyze the perceptions of non-Open University employees regarding social changes in the work system during the pandemic and their implications for post-pandemic work models. The study used a quantitative approach through a survey of 199 respondents, supported by in-depth interviews. The results of the study show that WFH provides flexibility and increased use of digital technology, but poses obstacles in concentration and work time limits. In contrast, WFO is more effective in coordination and social interaction. The main findings show that the hybrid work model is the dominant choice for adapting to social changes in work. In addition, there is a tendency towards the Work From Anywhere (WFA) system as a form of output-based work flexibility. This research confirms that the transformation of the work system is not only technical, but also reflects changes in work habits and social structures in modern organizations.